2016
DOI: 10.1371/journal.pgen.1006414
|View full text |Cite
|
Sign up to set email alerts
|

Budding Yeast Rif1 Controls Genome Integrity by Inhibiting rDNA Replication

Abstract: The Rif1 protein is a negative regulator of DNA replication initiation in eukaryotes. Here we show that budding yeast Rif1 inhibits DNA replication initiation at the rDNA locus. Absence of Rif1, or disruption of its interaction with PP1/Glc7 phosphatase, leads to more intensive rDNA replication. The effect of Rif1-Glc7 on rDNA replication is similar to that of the Sir2 deacetylase, and the two would appear to act in the same pathway, since the rif1Δ sir2Δ double mutant shows no further increase in rDNA replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 84 publications
2
33
0
Order By: Relevance
“…We found that rif1D caused significantly earlier recruitment at all three of these late-replicating telomere-proximal sites ( Figure 1A, right panel) and obtained similar results for origins close to the end of chromosome I-L ( Figure S1B). This effect is not due to telomere elongation caused by chronic absence of Rif1 (as in rif1D cells), because we observed the same phenotype after only 1 hr of anchor-away depletion of Rif1 (Haruki et al, 2008;Shyian et al, 2016), during which time telomere elongation is negligible ( Figure S1C).…”
Section: Scrif1 Affects the Timing Of Dna Polε Recruitment To Replicamentioning
confidence: 51%
See 2 more Smart Citations
“…We found that rif1D caused significantly earlier recruitment at all three of these late-replicating telomere-proximal sites ( Figure 1A, right panel) and obtained similar results for origins close to the end of chromosome I-L ( Figure S1B). This effect is not due to telomere elongation caused by chronic absence of Rif1 (as in rif1D cells), because we observed the same phenotype after only 1 hr of anchor-away depletion of Rif1 (Haruki et al, 2008;Shyian et al, 2016), during which time telomere elongation is negligible ( Figure S1C).…”
Section: Scrif1 Affects the Timing Of Dna Polε Recruitment To Replicamentioning
confidence: 51%
“…Conversely, for many origins farther from telomeres, and not Rap1-associated, the Rif1-RBM mutant showed higher ChEC signal compared to WT ( Figure 4B, for examples of two telomere-distal late ARSs; Figure 4C, red signal in the RBM/WT heatmap). One notable example of this effect is seen at the repetitive rDNA locus, where Rif1 inhibits the firing of an origin present in each of the 150-200 rDNA copies (Shyian et al, 2016). Two sites of enhanced Rif1-MNase cleavage are detected in the rDNA: one at the promoter of TAR1, which contains a Rap1 binding site, and a second at the rDNA origin, where no nearby Rap1 binding is observed ( Figure S4F).…”
Section: Rif1 Origin Binding Is Regulated By Rap1-dependent Telomere mentioning
confidence: 98%
See 1 more Smart Citation
“…We have also found that fresh cln3 mutants with a small rDNA copy number have no growth defects (not shown). The defects in rDNA silencing by Sir2 affect DNA replication and promote increased ARS firing and DNA recombination, which lead to genome instability and lethality [46]. The decreased Sir2 activity in the cln3 low repeat copy number may cause increased cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this highly repetitive structure and active transcriptional status, rDNA is the most recombinogenic, and therefore mutagenic, site within the eukaryotic genome (Nomura, 2001; Tomson et al, 2006; Pal et al, 2018; Kwan et al, 2016). The importance of maintaining rDNA locus stability is highlighted by the fact that DNA replication forks are programmed to stall within rDNA, precluding catastrophic head-on collision of replication and transcription complexes (Biswas et al, 2017; Weitao et al, 2003; Shyian et al, 2016). Furthermore, rDNA transcription rates, and even nucleolar size, are intimately coupled to changes in nutrient levels, revealing that rDNA plays a central role in responding to environmental cues (Li et al, 2006; Tsang et al, 2007; Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%